Mini-fluid Challenge of 100 ml of Crystalloid Predicts Fluid Responsiveness in the Operating Room. (September 2017) - Biais, Matthieu; de Courson, Hugues; Lanchon, Romain; Pereira, Bruno; Bardonneau, Guillaume; Griton, Marion; Sesay, Musa; Nouette-Gaulain, Karine
Abstract : Background: Mini-fluid challenge of 100 ml colloids is thought to predict the effects of larger amounts of fluid (500 ml) in intensive care units. This study sought to determine whether a low quantity of crystalloid (50 and 100 ml) could predict the effects of 250 ml crystalloid in mechanically ventilated patients in the operating room. Methods: A total of 44 mechanically ventilated patients undergoing neurosurgery were included. Volume expansion (250 ml saline 0.9%) was given to maximize cardiac output during surgery. Stroke volume index (monitored using pulse contour analysis) and pulse pressure variations were recorded before and after 50 ml infusion (given for 1 min), after another 50 ml infusion (given for 1 min), and finally after 150 ml infusion (total = 250 ml). Changes in stroke volume index induced by 50, 100, and 250 ml were recorded. Positive fluid challenges were defined as an increase in stroke volume index of 10% or more from baseline after 250 ml. Results: A total of 88 fluid challenges were performed (32% of positive fluid challenges). Changes in stroke volume index induced by 100 ml greater than 6% (gray zone between 4 and 7%, including 19% of patients) predicted fluid responsiveness with a sensitivity of 93% (95% CI, 77 to 99%) and a specificity of 85% (95% CI, 73 to 93%). The area under the receiver operating curve of changes in stroke volume index induced by 100 ml was 0.95 (95% CI, 0.90 to 0.99) and was higher than those of changes in stroke volume index induced by 50 ml (0.83 [95% CI, 0.75 to 0.92]; P = 0.01) and pulse pressure variations (0.65 [95% CI, 0.53 to 0.78]; P < 0.005). Conclusions: Changes in stroke volume index induced by rapid infusion of 100 ml crystalloid predicted the effects of 250 ml crystalloid in patients ventilated mechanically in the operating room. Abstract : The authors provide a prospective trial demonstrating that a mini-fluid challenge of 100 ml can predict the hemodynamic effects of larger fluid boluses in neurosurgical patients. The study has important implications to future fluid challenge algorithms and patient management to maximize hemodynamic stability and minimize the risk of fluid overload in the operating room.